2017
DOI: 10.2220/biomedres.38.41
|View full text |Cite
|
Sign up to set email alerts
|

<b>CD44 variant 9 expression as a predictor for gastric cancer recurrence: immunohistochemical and metabolomic analysis of surgically resected </b><b>tissues </b>

Abstract: CD44 variant 9 (CD44v9) and the heavy chain of 4F2 cell-surface antigen (CD98hc) appear important for regulation of reactive oxygen species defence and tumor growth in gastric cancer. This study examined the roles of CD44v9 and CD98hc as markers of gastric cancer recurrence, and investigated associations with energy metabolism. We applied capillary electrophoresis time-of-flight mass spectrometry to metabolome profiling of gastric cancer specimens from 103 patients who underwent resection with no residual tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…Different from the typical CD44 standard isomers, CD44 variants (CD44v) are considered to be the key molecules in the process of malignant transformation, and their expression is highly restricted and specific [52,53]. In general, CD44v, is considered to be a marker of GC cells [54,55], which help to increase resistance to chemotherapy or radiation-induced cell death [56][57][58][59][60][61][62][63][64][65]. Our results indicated that the expression of CD44 in GC was higher than that in normal tissues, and there was a positive correlation between CD44 and GAPDH.…”
Section: Discussionmentioning
confidence: 99%
“…Different from the typical CD44 standard isomers, CD44 variants (CD44v) are considered to be the key molecules in the process of malignant transformation, and their expression is highly restricted and specific [52,53]. In general, CD44v, is considered to be a marker of GC cells [54,55], which help to increase resistance to chemotherapy or radiation-induced cell death [56][57][58][59][60][61][62][63][64][65]. Our results indicated that the expression of CD44 in GC was higher than that in normal tissues, and there was a positive correlation between CD44 and GAPDH.…”
Section: Discussionmentioning
confidence: 99%
“…Yamakawa et al. performed metabolic profiling to differentiate tumor types of gastric cancer and Saito et al. profiled low molecular weight compounds in hepatocellular carcinoma .…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…CD44 expression has been associated with gastric cancer disease progression and aggressiveness [12,31,32], revealing its importance in these types of malignancies. In order to evaluate the impact of truncated O-glycans cellular profile, we first determined the product of alternative splicing of the CD44 gene in the presented models.…”
Section: Total Cd44 and Cd44v9 Expression In Gastric Cancer Cell Linementioning
confidence: 99%
“…The CD44v8-10 has been claimed to be the predominant CD44 variant found in gastric CSCs from patient tumor samples [9], and its expression was shown to promote resistance against reactive oxygen species (ROS) and contributed to cell proliferation [10]. Particularly, CD44v9, contained in CD44v8-10, is one of the major isoforms in human gastrointestinal cancer [11], and its presence is related to elevated tumor sizes and poor prognosis and survival [12,13]. Moreover, the mechanistic importance of CD44v9 highlights its potential as a promising biomarker and potential target in therapeutic strategies in GC.…”
Section: Introductionmentioning
confidence: 99%